MEMAHAMI NILAI-NILAI PANCASILA MELALUI BUDAYA LITERASI - Octaviona, Era; Zaki, Ahmad; Putri, Gita Leviana (Jurnal El-Pustaka, 2020)
In the era of global competition the meaning of "Pancasila" seems to have been forgotten by the Society. The history of formulating Pancasila was obtained through a long and long process carried out by the founding fathers of this country. The value of Pancasila must continue to be passed on to future generations so that it is maintained and preserved as values in the life of the nation and state, one of the steps in this effort is to improve the literacy culture of today's young generation to make it better. They do not easily describe and understand the true values of Pancasila. So that the literacy culture that we are promoting can again encourage the creation of the Indonesian nation so that it is not easily provoked, review various news that is heard to avoid divisions, fights, and incitement between the nations themselves.